Tipifarnib in Head and Neck Squamous Cell Carcinoma With HRAS Mutations. Issue 17 (10th June 2021) - Ho, Alan L.; Brana, Irene; Haddad, Robert; Bauman, Jessica; Bible, Keith; Oosting, Sjoukje; Wong, Deborah J.; Ahn, Myung-Ju; Boni, Valentina; Even, Caroline; Fayette, Jerome; Flor, Maria José; et al.
Abstract : PURPOSE: Mutations in the HRAS (m HRAS ) proto-oncogene occur in 4%-8% of patients with recurrent and/or metastatic (R/M) head and neck squamous cell carcinoma (HNSCC). Tipifarnib is a farnesyltransferase inhibitor that disrupts HRAS function. We evaluated the efficacy of tipifarnib in patients with R/M m HRAS HNSCC. METHODS: We enrolled 30 patients with R/M HNSCC in a single-arm, open-label phase II trial of tipifarnib for m HRAS malignancies; one additional patient was treated on an expanded access program. After an ad hoc analysis of the first 16 patients with HNSCC with m HRAS variant allele frequency (VAF) data, enrollment was limited to those with a m HRAS VAF of ≥ 20% (high VAF). The primary end point was objective response rate. Secondary end points included assessing safety and tolerability. Patients received tipifarnib 600 or 900 mg orally twice daily on days 1-7 and 15-21 of 28-day cycles. RESULTS: Of the 22 patients with HNSCC with high VAF, 20 were evaluable for response at the time of data cutoff. Objective response rate for evaluable patients with high-VAF HNSCC was 55% (95% CI, 31.5 to 76.9). Median progression-free survival on tipifarnib was 5.6 months (95% CI, 3.6 to 16.4) versus 3.6 months (95% CI, 1.3 to 5.2) on last prior therapy. Median overall survival was 15.4 months (95% CI, 7.0 to 29.7). The most frequent treatment-emergent adverse events among the 30 patients with HNSCC were anemia (37%) and lymphopenia (13%). CONCLUSION: Tipifarnib demonstrated encouraging efficacy in patients with R/M HNSCC with HRAS mutations for whom limited therapeutic options exist (NCT02383927 ).